Proposed new design for ESP retail shop at Lots 781 And 782, Section 57, Jalan Sultan Ismail, 55100 Kuala Lumpur, Wilayah Persekutuan / Mohd. Faritz Ahmad Shukri - Ahmad Shukri, Mohd. Faritz (Faculty of Architecture, Planning and Surveying, 2008)
Retail outlets have been growing in our country, Malaysia for the past decades with various kinds. Guitar stores and jamming studio have also growing, offering various kinds, brands and price range. Guitar Collection as a distributor of ESP(Electric Sound Product) is one of them, ESP has been increase from year to year in Malaysia. So, this is a good oppotumity to porpose a new design for ESP retail outlet only. The proposal of this project is Proposed New Design for ESP retail outlet at Lots 781 and 782, section 57, Jalan Sultan Ismail, 55100 Kuala Lumpur, Wilayah Persekutuan. A case study has been carried out to gain better knowledge about guitar stores and how it operates. Apart from client’s requirement, it gives the ideas of what the client might need. The case study has been done by interviewing the staffs, taking photos and excesses their website. During research, there are several issues has been discovered. Besides that, the research of interior space must also be considered as a case study. So, with that research, I can identified the problem where’s I can solve with guided from lecturer and proposed new design related